The new down towns : rebuilding business districts - Redstone, Louis G. (New York : McGraw Hill Education, 1976)
This book is written to present an appraisal of actual happenigs in cities of various sizes in the United States and in some other countries. This book will present some of the most significant examples of different approaches used to provide for the specific needs of each community. Examples will range from large, extensive transformations of entire core areas in the central business district in the large metropolises, as well as the smaller cities, to minimal improvements such as closing streets and creating malls for pedestrian use, using crossover connecting bridges, limiting auto traffic, and creating a more attractive atmosphere by means of landscaping, street furniture, special lighting, protective canopies, etc.
Foreword -- Overview -- Acknowledgments -- 1. Initiating CBD renewal: various approaches -- 2. Elements of CBD redevelopment -- 3. Significant case studies -- 4. Projects in planning and initial implementation stages -- 5. Preservation and restoration of historic buildings in the central business district area.
Keywords: URBAN RENEWAL -- UNITED STATES